Fermi Velocity and Effective Mass Variations in ZGaN Ribbons: Influence of Li-Passivation - Mandar Jatkar (IEEE, 2021)
The paper presents the structural stability and electronic properties of Zigzag Gallium Nitride nano ribbons(ZGaNNR) by considering the lithium(Li) atom by employing density functional theory (DFT). Li atom has been considered as a passivating element at various symmetric sites. By using Li atoms, a significant impact has been observed on the structural and electronic characteristics of ZGaNNRs. Bare@edges_both structure emerged to be the most energetically stable among other structures. For Li-passivation@edge_Ga structures, the minimum band gap has been noticed for III-V group family of nanoribbons. Interestingly, other structures of ZGaNNRs turn metallic nature irrespective of the Li site. Further, Li-bare@edge_N structure possesses the highest Fermi velocity as compared to other structures. This is useful for designing high speed interconnect applications. Further, we investigated the effective mass of various Li-ZGaNNR structures using standard two probe models. The effective mass of H-bare@edge_N structure reveals the highest effective mass in both valence and conduction bands. The proposed work proves the high capability towards the designing of the nano-scale devices.